Aplikasi Pencatatan Transaksi Keluar Masuk Dan Peramalan Obat Menggunakan Single Exponential Smoothing Pada Apotek Farmata - Prabowo, Andi; Sulistiowati, Sulistiowati; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Apotek Farmata is a pharmacy that sells various kinds of medicinal equipment. With these drugs, consumers can find the drugs they need. The problem that is currently occurring at the Farmata Pharmacy is that the Pharmacy Admin does not know exactly how many drugs will be ordered for the following month, this has resulted in some drug requests by customers not being fulfilled because drug supplies cannot meet consumer demand. Based on the above problems, the solution offered is an application for recording drug in and out transactions which will be integrated with the Single Exponential Smoothing method. The Single Exponential Smoothing method is a method used to forecast the average drug demand data every month and is not influenced by trends or seasons. In this study, the Single Exponential Smoothing method is used because the level of error is relatively small. This is done so that the drug does not pass the expiration date. The application produced in this study is the application of recording transactions in and out of and forecasting drugs at Pharmacies Farmata using Single Exponential Smoothing. The results of application testing with black-box testing are that every function of the application is running well.